Productivity Growth in OIC Countries: SDGs Perspective - Rusydiana, Aam Slamet; Ningsih, Rachmi Ramdia (Islamic Economics Methodology, 2024)
Over the past few decades, countries in the Organization of Islamic Cooperation (OIC) have achieved various levels of economic development. In today's sustainable era, increasing efficiency and productivity is one of the goals to be achieved. Development goals, especially the achievement of food security, healthy lives and well-being for all ages, gender equality, inclusive economic growth, and industrialization are important to ensure access to sustainable livelihoods. This study aims to assess changes in total factor productivity and efficiency based on n indicators of sustainable development goals (SDGs) in 49 countries that are members of the OIC during the period 2010 to 2017. Utilizing the Malmquist total factor productivity (TFP) index and Data Envelopment Analysis (DEA), this study estimates the changes in productivity and efficiency that occurred in each OIC member country. The results show that Jordan, Cameroon, Tunisia, Saudi Arabia, and Lebanon are the countries with the highest TFP increase in the observed years. However, the overall productivity of OIC countries has decreased as evidenced by the Malmquist TFP index which is less than one or 0.991. This productivity decline is caused by technical and technological inefficiencies. On the other hand, there are differences in productivity in countries belonging to the GCC, AMU, Sub-Saharan Africa, Middle East countries, and Asian countries. The performance comparison is intended to help identify policies for further improvement for OIC countries in the region.